A bioengineered lymphatic vessel model for studying lymphatic endothelial cell‐cell junction and barrier function. (4th October 2021) - Henderson, Aria R.; Ilan, Isabelle S.; Lee, Esak
Abstract: Objective: Lymphatic vessels (LVs) maintain fluid homeostasis by draining interstitial fluid. A failure in lymphatic drainage triggers lymphatic diseases such as lymphedema. Since lymphatic drainage is regulated by lymphatic barrier function, developing experimental models that assess lymphatic barrier function is critical for better understanding of lymphatic physiology and disease. Methods: We built a lymphatic vessel‐on‐chip (LV‐on‐chip) by fabricating a microfluidic device that includes a hollow microchannel embedded in three‐dimensional (3D) hydrogel. Employing luminal flow in the microchannel, human lymphatic endothelial cells (LECs) seeded in the microchannel formed an engineered LV exhibiting 3D conduit structure. Results: Lymphatic endothelial cells formed relatively permeable junctions in 3D collagen 1. However, adding fibronectin to the collagen 1 apparently tightened LEC junctions. We tested lymphatic barrier function by introducing dextran into LV lumens. While LECs in collagen 1 showed permeable barriers, LECs in fibronectin/collagen 1 showed reduced permeability, which was reversed by integrin α5 inhibition. Mechanistically, LECs expressed inactivated integrin α5 in collagen 1. However, integrin α5 is activated in fibronectin and enhances barrier function. Integrin α5 activation itself also tightened LEC junctions in the absence of fibronectin. Conclusions: Lymphatic vessel‐on‐chip reveals integrin α5 as a regulator of lymphatic barrier function and provides a platform for studying lymphatic barrier function in various conditions.